The Impact of Versatile Macrophage Functions on Acute Kidney Injury and Its Outcomes - Baek, Jea-Hyun (Frontiers in Physiology, 2019)
Acute kidney injury (AKI) is a common and devastating clinical condition with a high morbidity and mortality rate and is associated with a rapid decline of kidney function mostly resulting from the injury of proximal tubules. AKI is typically accompanied by inflammation and immune activation and involves macrophages (M) from the beginning: The inflamed kidney recruits “classically” activated (M1) M, which are initially poised to destroy potential pathogens, exacerbating inflammation. Of note, they soon turn into “alternatively” activated (M2) M and promote immunosuppression and tissue regeneration. Based on their roles in kidney recovery, there is a growing interest to use M2 Mand M-modulating agents therapeutically against AKI. However, it is pertinent to note that the clinical translation of M-based therapies needs to be critically reviewed and questioned since M are functionally plastic with ambiguous roles in AKI and, more importantly, M2 M increase the risk for the development of interstitial fibrosis and subsequent chronic kidney disease (CKD). In this review, we discuss the current state of knowledge on the biology of different M subtypes during AKI and, especially, on their impact on AKI and assess the net effect of ambiguous M functions in AKI based on the findings from translational AKI studies.